2019
DOI: 10.1111/wvn.12364
|View full text |Cite
|
Sign up to set email alerts
|

A Multicountry Study on Nursing Students’ Self‐Perceived Competence and Barriers to Evidence‐Based Practice

Abstract: BackgroundNursing education and training are essential in the attainment of evidence‐based practice (EBP) competence in nursing students. Although there is a growing literature on EBP among nursing students, most of these studies are confined to a single cultural group. Thus, cross‐cultural studies may provide shared global perspectives and theoretical understandings for the advancement of knowledge in this critical area.AimsThis study compared self‐perceived EBP competence among nursing students in four selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
5
16
0
4
Order By: Relevance
“…8 Evidence-based practice competency is getting more and more attention globally, and most studies have focused on students in nursing field. [9][10][11] Actually, nurses working in kinds of health care settings at the frontline are the protagonists to carry out EBP for better nursing service. A set of clear EBP competency for both practicing registered nurses and advanced practice nurses in clinical settings was developed by several nursing leaders.…”
Section: Inquirymentioning
confidence: 99%
“…8 Evidence-based practice competency is getting more and more attention globally, and most studies have focused on students in nursing field. [9][10][11] Actually, nurses working in kinds of health care settings at the frontline are the protagonists to carry out EBP for better nursing service. A set of clear EBP competency for both practicing registered nurses and advanced practice nurses in clinical settings was developed by several nursing leaders.…”
Section: Inquirymentioning
confidence: 99%
“…Nevertheless, international studies show a high variability at EBP competency of undergraduate nursing students [ 16 , 17 ]. The literature indicates that many nursing students are not very much engaged in EBP use and struggle to see the relevance of evidence for nursing practice due to lack of knowledge and skills, non-positive attitude towards EBP in students, faculties and nurses as well as the lack of support in clinical settings [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[38] Furthermore, students who have been involved in oral presentations and journal clubs have found it helpful to analyse and discuss the findings of EBP [39] and are more likely to improve their EBP knowledge and skills. [13] The current study demonstrated that the research coach model helped students achieve basic knowledge in EBP to translate knowledge. The health and healing course integrated EBP concepts and were perceived as effective when students were provided with an avenue to connect the relationship of EBP concepts to case studies.…”
Section: Participant's Characteristicsmentioning
confidence: 66%
“…[10,11] Higher education levels and greater clinical experience are associated with increased self perceived EBP competence and clinical decision making in students. [12,13] Hence, nursing students require confidence in their ability to engage with EBP in their practice. Challenges in evidence gathering skills in accessing, utilizing, and appraising EBP information are the main themes in understanding the importance of evidence for practice.…”
Section: Scholarshipmentioning
confidence: 99%
See 1 more Smart Citation